2021
DOI: 10.4081/ecj.2021.9859
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 management in Emergency Department: risk stratification and care setting identification proposal based on first pandemic wave in Pisa University Hospital

Abstract: SARS-CoV-2 management in Emergency Department: risk stratification and care setting identification proposal based on first pandemic wave in Pisa University Hospital Background: COVID-19 patients require early treatment and admission to an appropriate care setting, considering possible rapid and unpredictable to Severe Acute Respiratory Syndrome. Objective: A flow-chart was developed by a multidisciplinary team of Emergency Department (ED) clinicians, intensivists and radiologists aiming to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…19 A progressive improvement in COVID patient mortality has been described, 20,21 but this was not demonstrated in our cohort's three consecutive waves. The reduction in mortality is most likely the result of a multifactorial process that cannot be well interpreted Male sex, cardiovascular comorbidities, acute cardiac or kidney injury, lymphocytopenia, and D-dimer were all associated with an increased risk of in-hospital death, 8,22,23 but none of these variables were found to be predictors in our study.…”
Section: Articlecontrasting
confidence: 57%
“…19 A progressive improvement in COVID patient mortality has been described, 20,21 but this was not demonstrated in our cohort's three consecutive waves. The reduction in mortality is most likely the result of a multifactorial process that cannot be well interpreted Male sex, cardiovascular comorbidities, acute cardiac or kidney injury, lymphocytopenia, and D-dimer were all associated with an increased risk of in-hospital death, 8,22,23 but none of these variables were found to be predictors in our study.…”
Section: Articlecontrasting
confidence: 57%
“…Baseline characteristics of our study population, dating back to the very first pandemic wave, showed a high prevalence of males, cardiovascular diseases and hospital management influenced not only by clinical conditions but also by organizational difficulties [22] , [23] , [24] , [25] .…”
Section: Discussionmentioning
confidence: 99%